Bioecological features of apple ermine moth in the Dzungar and trans-Ili Alatau (Journal of Geography and Environmental Management, 2020)
The article describes results of the study of bioecological development features of the apple ermine moth Hyponomeuta malinellus Zell. in the Trans-Ili Alatau and Dzungar Alatau state national parks. The work’s main objective is to reveal the factors influencing the pest development, determine the phenological and environmental characteristics, and identify the most vulnerable development stage of the apple ermine moth Hyponomeuta malinellus Zell., in order to apply appropriate timely measures controlling the pest. In the course of the study, the exact dates and abiotic factors were established. The results of the study activity of apple ermine moths were summarized, and a phenological calendar for the development of this pest has also been compiled. The pest developed in one generation, in the foothill zone of the Almaty region on the territory of the Trans-Ili Alatau and Dzungar Alatau state national parks in 2018–2019. The duration of the particularly dangerous period of the pest, depending on weather conditions, is from 37 to 45 days. In order to fight this pest, accurate knowledge of the phenological and environmental data is very important. During the 2018–2019 years, the pest, under conditions of the foothill zone of the Almaty region, in the area of the Trans-Ili Alatau and Dzungar Alatau state national parks, developed during one generation. The period particularly dangerous for the pest lasts 37 to 45 days, depending on weather conditions. To control the pest, scientists need to have accurate phenological and environmental data.
Keywords: ermine apple moth, the Sievers apple, the Dzungar Alatau, the Trans-Ili Alatau.